Epidemiology of chronic inflammatory demyelinating polyneuropathy abroad and in Russia - T. E. Popova; N. A. Shnayder; M. M. Petrova; T. Ya. Nikolaeva; E. A. Kantimirova (Нервно-мышечные болезни, 2015)
Current article provides an overview of the results of epidemiological studies of chronic inflammatory demyelinating polyneuropathy (CIDP) in Russia and abroad. It is shown that the prevalence of CIDP is different in countries, due to the use of different diagnostic criteria. It should be noted that the reliability of epidemiological prevalence and incidence is affected by difficulties of diagnosis of atypical forms of the disease.